Exposure of human fetal kidneys to mild analgesics interferes with early nephrogenesis. Issue 7 (9th June 2021) - Leverrier‐Penna, Sabrina; Michel, Alain; Lecante, Laetitia L.; Costet, Nathalie; Suglia, Antonio; Desdoits‐Lethimonier, Christèle; Boulay, Hugoline; Viel, Roselyne; Chemouny, Jonathan M.; Becker, Emmanuelle; Lavoué, Vincent; Rolland, Antoine D.; et al.
Abstract: Acetaminophen, aspirin, and ibuprofen are mild analgesics commonly used by pregnant women, the sole current recommendation being to avoid ibuprofen from the fifth month of gestation. The nephrotoxicity of these three analgesics is well documented in adults, as is their interference with prostaglandins biosynthesis. Here we investigated the effect of these analgesics on human first trimester kidneys ex vivo. We first evaluated prostaglandins biosynthesis functionality by performing a wide screening of prostaglandin expression patterns in first trimester human kidneys. We demonstrated that prostaglandins biosynthesis machinery is functional during early nephrogenesis. Human fetal kidney explants aged 7‐12 developmental weeks were exposed ex vivo to ibuprofen, aspirin or acetaminophen for 7 days, and analyzed by histology, immunohistochemistry, and flow cytometry. This study has revealed that these analgesics induced a spectrum of abnormalities within early developing structures, ranging from cell death to a decline in differentiating glomeruli density. These results warrant caution for the use of these medicines during the first trimester of pregnancy.